Strengthening Character Through Anti-Bullying Socialization Among Junior High School Students: Penguatan Karakter Melalui Sosialisasi Anti Bullying pada Kalangan Pelajar SMP - Hamzah, Munira; Faisal, Andi Fahri; Hasan, Hasan; Wibowo, Hadi Yudho Prio; Jumriani, Jumriani (Jurnal Inovasi dan Pengabdian Kaa Mieera, 2025)
Bullying is an act of intentionally hurting an individual or group verbally, physically, psychologically, or socially, with serious impacts on victims. According to data from the Indonesian Child Protection Commission (KPAI) in 2024, cases of physical and psychological abuse against children increased from 7.8% in 2023 to 11.7% in 2024. In response to this, the community service team from UNSULBAR conducted an anti-bullying awareness program at SMPN 6 Wonomulyo. This activity aimed to improve students’ understanding, attitudes, and behavior in preventing and responding to bullying. The program consisted of three stages: preparation, implementation, and evaluation. The awareness campaign was delivered through interactive education, short educational films, group discussions, and quizzes with prizes to encourage active participation. The material covered types of bullying (verbal, physical, relational, and cyber), the roles involved in bullying incidents, and practical ways to handle them. A total of 73 students participated in the activity, which was positively received by students and school staff. Evaluation was conducted via Q&A sessions and direct feedback from students and teachers. The results showed increased student awareness and a collective commitment to fostering a safe and inclusive school environment.